Moderate/high resistance exercise is better to reduce blood glucose and blood pressure in middle-aged diabetic subjects - Sousa, Ricardo Augusto Leoni de (2020)
Type 2 diabetes (T2D) main feature is insulin resistance. Hypertension is a comorbidity linked to T2D. Resistance exercise (RE) is an important non-pharmacological tool to contribute to managing blood glucose and blood pressure (BP), but there is not a common sense about acute effects. The aim of this study was to evaluate the acute physiological effects after two different RE sessions using different intensities at middle-aged hypertensive T2D subjects. There were 40 middle-aged men (20 nondiabetics; 20 diabetics), who underwent an exercise protocol with the same volume at 60% or 75% of the one maximum repetition test (1RM), consisting in: bench press, triceps pulley, rowing machine, barbell curl, lateral raise with dumbbells and barbell squat. Physiological changes were evaluated through BP, glycemia, creatine kinase, lactate dehydrogenase, C reactive protein (C-RP), testosterone and cortisol.For non-diabetics, both intensities promoted blood glucose uptake (8.2% to 11.1%, p<0.05), and only the 75%1RM session induced blood glucose uptake in 5.7% in the diabetics. Post-exercise hypotension was significant after RE at 75%1RM for systolic BP (SBP) and after both intensities for diastolic BP (DBP) in non-diabetics, while the SBP and DPB reduced after both intensities for diabetics. RE at 75%1RM resulted in better blood glucose uptake, and both intensities reduced the BP in diabetic subjects. After 75%1RM there was a higher indirect muscle damage result. The alterations in hormones, C-RP, and indirect muscle damage markers indicated an adequate acute anabolic recovery with no significant inflammation in both intensities. Acute RE at 60%1RM or 75%1RM can used as an extra tool to manage both pathologic conditions.